Basic Design Management Accounting System for Simple Village-Owned Enterprises - Nadeak, Putry Handayani; Nazmudin, Adin Syaeful; Aprianti, Ajeng Dwi; Muliawati, Ayu; Brata, Ignatius Oki Dewa (International Journal of Psychosocial Rehabilitation, 2020)
Indonesia is a country that has a populist economic policy. The government policy is to drive the village economy is a very smart idea. This policy is expected for the future becomes one of the pillars of the country's economy. Those various problems arise in the way this Village-Owned Enterprises goes, the problem most often arises is lack of human resources, and organizational management is not good enough. The research designed to develop the basic Accounting Information System to help more or simple Village-Owned Enterprises can be organized the entity better than before. Through this basic design Village-Owned Enterprises can begin to develop parts within the entity. Otherwise, the Village-Owned Enterprises can develop much better and more complete in the future. This basic cycle are important to very important to exist in basic Village-Owned Enterprises, so the entity can start to make business activity, and continuous update or redesign the Accounting Information System as far as entities can grow. The researchers hope these three cycles can help their operational performance to be structured and improve the performance and quality of the village-owned enterprises, however,they are more advanced and able to contribute to the government, especially to develop the village arround.